Base-Superstructure Relations and the Transformation of Class Consciousness in Novel Guru Aini by Andrea Hirata: Literary Sociology Studies of Karl Marx - Mahmudah Mahmudah; Nur Nadiyah Herman; Sinar Ansar; Nur Hikma; Wilda Wijayanti; Nurhaeni Nurhaeni (Badan Pengembangan dan Pembinaan Bahasa, 2026)
The gap in access to education for the lower class is a structural problem that is not only present in social reality but is also represented in literary works. The novel Guru Aini by Andrea Hirata reflects this problem through the relationship between material conditions and the ideological structure of society. However, previous studies tend to be descriptive and have not revealed the dialectical relationship between bases and superstructures in depth. This study aims to analyze the base-superstructure relationship and the transformation of class consciousness in the novel using the perspective of Karl Marx's social criticism. The method used is qualitative descriptive with a sociological approach to Karl Marx's literature. Data in the form of text excerpts that represent aspects of base, superstructure, and collective consciousness are collected using reading and recording techniques. Data collection was carried out through the reading and note-taking technique. The steps include: (1) reading the novel thoroughly and carefully; (2) identifying and marking the relevant parts of the text with the analysis category; (3) recording the data into a data card containing citations, page numbers, and category codes, while the analysis follows the Miles and Huberman model, which includes data reduction, data presentation, and conclusions drawn. Data analysis is carried out through the stages of data condensation, data identification, interpretation, and conclusion drawn. The results of the study show that the base is represented through structural poverty, limited access to education, and unequal production relations, while the suprastructure exists as an ambivalent education system, which reproduces inequality while opening up the space for emancipation. The transformation of the class consciousness of the character takes place through contradictory experiences that encourage the emergence of a critical awareness of an unjust system. Abstrak Kesenjangan akses pendidikan bagi kelas bawah merupakan persoalan struktural yang tidak hanya hadir dalam realitas sosial, tetapi juga direpresentasikan dalam karya sastra. Novel “Guru Aini” karya Andrea Hirata mencerminkan persoalan tersebut melalui relasi antara kondisi material dan struktur ideologis masyarakat. Namun, kajian sebelumnya cenderung bersifat deskriptif dan belum mengungkap hubungan dialektis antara basis dan superstruktur secara mendalam. Penelitian ini bertujuan untuk menganalisis relasi basis-superstruktur dan transformasi kesadaran kelas dalam novel tersebut menggunakan perspektif kritik sosial Karl Marx. Metode yang digunakan adalah kualitatif deskriptif dengan pendekatan sosiologi satra Karl Marx. Data berupa kutipan teks yang merepresentasikan aspek basis, superstruktur, dan kesadaran kolektif, data dikumpulkan teknik baca dan catat. Pengumpulan data dilakukan melalui teknik baca-catat (reading and note-taking). Langkah-langkahnya meliputi: (1) membaca novel secara menyeluruh dan cermat; (2) mengidentifikasi dan menandai bagian-bagian teks yang relevan dengan kategori analisis; (3) mencatat data ke dalam kartu data yang memuat kutipan, nomor halaman, dan kode kategori, sedangkan analisis mengikuti model Miles dan Huberman yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Analisis data dilakukan melalui tahapan kondensasi data, identifikasi data, interpretasi dan penarikan simpulan. Hasil penelitian menunjukkan bahwa basis direpresentasikan melalui kemiskinan struktural, keterbatasan akses pendidikan, dan relasi produksi yang timpang, sedangkan suprastruktur hadir sebagai sistem pendidikan yang bersifat ambivalen, yakni mereproduksi ketimpangan sekaligus membuka ruang emansipasi. Transformasi kesadaran kelas tokoh berlangsung melalui pengalaman kontradiktif yang mendorong munculnya kesadaran kritis terhadap sistem yang tidak adil.